Impact of single-dose intravenous paracetamol on lymphocyte DNA damage and oxidative stress in trauma patients. - Sogut, Ozgur; Solduk, Leyla; Gokdemir, Mehmet Tahir; Kaya, Halil (My University, 2015)
We investigated the impact of paracetamol administration on lymphocyte DNA damage and oxidative stress parameters for acute pain management in patients with acute trauma-related pain. Thirty-five adult patients with mild or moderate trauma and 33 eligible healthy volunteers as control subjects were enrolled. Blood samples were obtained from the patients before and at 2 and 12 h after IV administration of paracetamol. Serum lymphocyte DNA damage and total oxidant status (TOS), total antioxidant status (TAS) and oxidative stress index (OSI) were studied as oxidative stress parameters. Serum lymphocyte DNA damage levels were 14.97 +/- 12.38 AU (arbitrary units) in Group 1 (before analgesia), 13.94 +/- 9.28 AU in Group 2 (2 h after analgesia), and 10.57 +/- 8.73 AU in Group 3 (12 h after analgesia). A significant difference was observed among the groups with respect to serum lymphocyte DNA damage (p < 0.01). Mean serum TOS and OSI values were lower in Groups 2 and 3 compared to that in Group 1. Furthermore, mean serum TAS values were higher in Group 3 compared to that in Goup 1. Our data suggest that the treatment of trauma-related acute pain with intravenous paracetamol resulted in decreased DNA damage in human T lymphocytes.